Microplastic abundance in sediments of the artificial ponds at Mulawarman University, Samarinda, East Kalimantan - Hamdhani, Hamdhani; Dania, Rahma; Jailani, Jailani (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2025)
Microplastics present in the environment, particularly in sediments, pose potential threats to aquatic organisms, as they can impair organ function when ingested. This study aims to assess the abundance, types, and colors of microplastics in the sediments of the artificial pond at Mulawarman University, Samarinda. The research employed a purposive sampling method. The Faculty of Agriculture pond had a higher microplastic abundance compared to the UNMUL HUB pond. Nonetheless, statistical analysis using a t-test showed no significant difference in microplastic levels between the two sites at Mulawarman University, Samarinda (p-value > 0.05). Overall, the artificial ponds at Mulawarman University, East Kalimantan, contained an average of 275 particles of microplastic per kilogram of dry sediment. Specifically, the Faculty of Agriculture pond had 161.25 particles/kg, while the UNMUL HUB pond had 113.75 particles/kg. The microplastics found consisted of fibers, fragments, films, and pellets, with colors including black, blue, red, brown, yellow, and white.